Will at the Battle of Gettysburg 1863 - Calkhoven, Laurie. (Boys of wartime, 2011)
In 1863, twelve-year-old Will, who longs to be a drummer in the Union army, is stuck in his sleepy hometown of Gettysburg, Pennsylvania, but when the Union and Confederate armies meet right there in his town, he and his family are caught up in the fight. Includes historical notes, glossary, and a timeline of events.